Whole-Mount Kidney Clearing and Visualization Reveal Renal Sympathetic Hyperinnervation in Heart Failure Mice - Wu, Chao; Yan, Fang; Li, Min; Tu, Yimin; Guo, Ziyu; Chen, Yufei; Wu, Yaxin; Li, Qing; Yu, Changan; Fu, Yi; Wu, Meihui; Kong, Wei; et al. (Frontiers in Physiology, 2021)
Developing a three-dimensional visualization of the kidney at the whole-mount scale is challenging. In the present study, we optimized mouse whole-mount kidney clearing, which improved the transparency ratio to over 90% based on organ-specific ligation (OSL)-clear, unobstructed brain imaging cocktails and computational analysis (CUBIC). The optimized OSL-CUBIC-compatible three-dimensional immunostaining and imaging simultaneously visualized the high-resolution three-dimensional structure of the whole-mount renal microvascular, glomerulus, and accompanying wrapped traveling sympathetic nerves in mice. A mouse model of pressure overload-induced heart failure was then established by minimally invasive transverse aortic constriction. Further three-dimensional quantification revealed renal sympathetic hyperinnervation (6.80% ± 1.04% vs. 3.73% ± 0.60%, P < 0.05) in mice with heart failure. In conclusion, this newly developed whole-organ tissue clearing and imaging system provides comprehensive information at the whole-mount scale and has great potential for kidney research. Our data suggest that renal sympathetic hyperinnervation is involved in heart failure associated renal dysfunction